Effect of Ammonium Sulfate on Flower and Pod Development of Soybean [Glycine max (L.) Merr.] - Devi Vira Setiana; Yulita Nurchayati; Nintya Setiari (Institut Pertanian Bogor, 2026)
Soybean [Glycine max (L.) Merr.] is a food crop rich in vegetable oil and protein, with increasing demand and economic worth. Increasing soybean production can be accomplished by providing nutrients nitrogen and sulfur, hence increasing the percentage of bloom development into pods. Applying ammonium sulfate at the start of planting can fulfill nitrogen and sulfur fertilizer requirements. The purpose of this study was to examine and determine the ideal concentration of ammonium sulfate for optimal flower and pod formation, as well as the percentage of flower development into pods and leaf sulfur content. Ammonium sulfate was applied in an experimental garden by mixing it into the planting material in polybags under controlled settings. This study employed a single-factor fully randomized design with four doses of ammonium sulfate. The treatments were ammonium sulfate [NH4)2SO4] at various concentrations of 0, 100, 200, and 300 kg/ha administered at the start of planting, with five replications. The research factors were the quantity of flowers, pods, percentage of flower development into pods, and sulfur level in the leaves. The sulfur content of the leaves was determined using an atomic absorption spectrophotometer. Data were analyzed using ANOVA at a significance level of 5%, followed by DMRT if the results were significant. The results revealed that ammonium sulfate 300 kg/ha produced the highest number of flowers, pods, percentage of flower development into pods, and sulfur content in leaves. Keywords: ammonium sulfate, nitrogen, productivity, soybean, sulfur